Understanding the Correlation Between Structure and Entangled Photon Pair Properties with Metal-Organic Frameworks - Herrera-Urbina, F; Fritz, R (American Chemical Society, 2023)
Spontaneous parametric down conversion (SPDC) is a quantum second-order nonlinear optical process where the photons generated are frequently used in quantum information processing. Materials with large second-order nonlinearities (χ(2)) can be used as entangled photon sources with a high brightness. The source brightness scales as the square of the effective nonlinearity (deff), which is an intrinsic property of the material. Understanding material factors that can significantly alter this intrinsic property is useful in developing new materials that are SPDC efficient. In our work we focus on understanding factors affecting the entangled photon pair properties, such as the arrangements of ligands within the Zn(3-ptz)2metal-organic framework (MOF) crystal and temperature. We find that the arrangement and alignment of the pyridine rings in the crystal structure significantly affect the deffand birefringence (Δn). Smaller pyridine ring alignments relative to the optic c-axis increase the Δn, which in turn leads to larger photon pair correlation times (τc) in coincidence measurements. Our work has significant implications in understanding the effect of ligand arrangement on deffand τcfor any MOF crystal structure, providing a tool to rationalize the optimization of MOF crystals for the development of efficient nonlinear optical devices. © 2023 American Chemical Society. All rights reserved.